Pengaruh Perencanaan Kebutuhan Bahan Baku Dan Pengendaliaan Persediaan Bahan Baku Terhadap Kelancaran Proses Produksi Pada PT. Batik Sakera - Diansyah, Diansyah; Yani, Ari Soeti; Giyanti, Giyanti (Innovative: Journal Of Social Science Research, 2025)
This study aims to analyze the effect of raw material requirements planning and inventory control on the smooth production process at PT. Batik Sakera. This study uses a quantitative approach with an explanatory research approach. The study population was all 45 employees in the production department of PT. Batik Sakera, who were also sampled using a census technique (non-probability sampling). Data were collected through questionnaires and analyzed using T-tests and F-tests. The research instruments were tested for validity and reliability. The results show that raw material requirements planning has a positive and significant effect on the smooth production process. Raw material inventory control has a positive and significant effect on the smooth production process. Raw material requirements planning and inventory control have a positive and significant effect on the smooth production process.